Isosorbide-Induced Decompression Effect on the Scala Media: Participation of Plasma Osmolality and Plasma Arginine Vasopressin. Issue 4 (April 2017) - Takeda, Taizo; Takeda, Setsuko; Uehara, Natsumi; Yanagisawa, Shungaku; Furukawa, Tatsuya; Nibu, Ken-ichi; Kakigi, Akinobu
Abstract : Objective: The correlation between the isosorbide-induced decompression effect on the endolymphatic space and plasma osmolality (p-OSM) or plasma arginine vasopressin (p-AVP) was investigated on comparing two different dosages of isosorbide (2.8 and 1.4 g/kg) to elucidate why the decompression effect is delayed with a large dose of isosorbide. Materials and Methods: Two experiments were performed using 80 guinea pigs. Experiment 1 was designed to morphologically investigate the sequential influence of the oral intake of 1.4- and 2.8-g/kg doses of isosorbide on the endolymphatic volume. The animals used were 50 guinea pigs (control: 10, experimental: 40). All animals underwent surgical obliteration of the endolymphatic sac of the left ear. One month after the surgery, control animals were sacrificed 3 hours after the intake of distilled water, and experimental animals were sacrificed 3 and 6 hours after the isosorbide intake. All of the left temporal bone served for the quantitative assessment of changes in the endolymphatic space, and the cross-sectional area of the scala media was measured from the mid-modiolar sections of the cochlea. Experiment 2 was designed to investigate changes in p-OSM and p-AVP levels 3 hours after the oral intake of isosorbide. Animals used were 15 guinea pigs (control: 5, experimental: 10). The control group received the oral administration of distilled water (4 ml/kg), and the experimental animals were subdivided into two groups consisting of 10 animals each by the dosage of isosorbide (1.4 or 2.8 g/kg). All animals were sacrificed for the measurement of p-OSM and p-AVP concentrations 3 hours after the intake of water or 70% isosorbide solution. Results: Morphologically, an isosorbide-induced decompression effect was noted in animals with both 1.4- and 2.8-g/kg doses of isosorbide. According to the regression analysis, however, the volumetric decrease of the endolymphatic space was more evident in cases with the small dose (1.4 g/kg) 3 hours after the intake (analysis of covariance [ANCOVA], p < 0.001). Six hours after, the decompression effect was significantly greater in cases with the large dose (2.8 g/kg) (ANCOVA, p < 0.001). Isosorbide intake caused a rise in p-OSM levels dose-dependently. The Cochran–Cox test revealed that the differences in the mean values among control and isosorbide groups were significant ( p < 0.01). Regarding the p-AVP level, a significant increase was evident in cases with the large dose (2.8 g/kg) ( p < 0.01, Cochran–Cox test), and not in cases with the small dose (1.4 g/kg). Conclusion: An isosorbide-induced decompression effect of the endolymphatic space was evident in spite of two different dosages of isosorbide (2.8 and 1.4 g/kg). Three hours after the isosorbide intake, however, the decompression effect was more marked in the group with the small dose (1.4 g/kg). Since significant rises in p-OSM and p-AVP were evident in the group with the large dose, this early rise of p-AVP due to dehydration seems to be the major reason for the delayed decompression effect in cases with a large isosorbide intake.